Analysis of Student Performance Data from a Computer Architecture and Organization Course - Moraes da Luz Brum, Luciano; Roberto Heinen, Milton; da Silva Camargo, Sandro (RENOTE, 2018)
Some known problems in the literature are the lack of interest and difficulty of students in Computer Architecture and Organization courses. We analyzed the students' performance in tests and semipresential learning activities in three editions of Introduction to Computer Architecture course from the Computer Engineering program of the Federal University of Pampa. We also analyzed the National High School Exam grades of these students, by knowledge area. The purpose of this study is to identify, through analytical processes using data from the course and grades of the NHSE, the most influential factors in the students’ first and final grades and subsidize the proposal of effective actions to solve the problem of high percentages of students’ failure.